New frontiers for self research - Marsh, Herbert W.; Craven, Rhonda G.; McInerney, D. M. 1948- (International advances in self research ;, 2005)
Researchers with the Self-concept Enhancement and Learning Facilitation Research (SELF) Centre, U. of Western Sydney, introduce theoretical issues and research on the relationship of positive/self-handicapping self-concept to success/ failure in academic and other settings.